Light and scanning electron microscopic characterization of pollen grains of some wetland angiosperms from India. Issue 7 (12th April 2022) - Paul, Payel; Dhar, Sayantan; Das, Dipayan; Chowdhury, Monoranjan
Abstract: Pollen grains of 58 wetland species of angiosperms belonging to 17 families, growing in different wetlands of Sub‐Himalayan biodiversity hotspots, Northern Bengal and lower Gangetic plains, India were investigated during a 4‐year span of 2015–2019. Freshly collected anthers were processed through the acetolysis method and the obtained pollen grains were accurately studied under LM and SEM and properly photographed. Different attributes viz. shape, size, aperture type and exine ornamentation of pollen grains served as consistent features were used for authentic identification of the studied species. To study the phylogeny of pollen grains, characters like polarity, symmetry, aperture and exine sculpturing were found most significant for species segregation. Investigated pollen grains were mostly prolate‐spheroidal, spheroidal or triangular, rarely prolate or elongated, exine psilate, granulate, reticulate or microechinate type. Most of the observable aperture of pollen grains of studied species were colporate, colpate and porate, while ulcerate and inaperturate grains were also observed in the studied aquatic members of the families Cyperaceae and Potamogetonaceae. All the gathered data were further statistically analyzed through ANOVA, PCA and Pearson Correlation Matrix to understand the interrelationship among the species. The permanent slides of identified pollen grains were deposited at the herbarium of North Bengal University [NBU] for future references. Highlights: Study of Pollen morphology of 58 wetland species under light & scanning electron microscopy. Unique apertures and exine ornamentation used to understand taxonomic evaluation of studied species. Pollen character supports interrelationship among the studied species. Relationship between exine thickness and the habitat of the wetland plants. Abstract : Taxonomic evaluation through microscopic characterization of some wetland angiosperm pollen grains